Career Decision-Making Competency,Self-Knowledge,And Occupational Explorations:A Model For University Students - Abdullah, Norida; Hussin, Noraini; Shonubi, Olurotimi Adebayo; Ghazali, Siti Raudzah; Abu Talib, Mansor (Penerbit UTHM, 2018)
University graduates are often lacking in soft-skills and job-seeking skill which affect their career decision-making skills.Therefore,the aim of the present study was to explore the factors that might potentially drive the career decision-making of graduates.Specifically,this study aims at developing a career decision-making competency model for effective career decision among graduating students.The sample for this research consisted of 1655 graduating students from universities in Malaysia.Participants were recruited using the cluster sampling method.Four instruments were used in this research namely,demographic information sheet,Self-Esteem scale,Job-search scale and Career decision-making scale. The instruments used were tested for their validity and reliability.Confirmatory Factor Analysis AMOS was used to obtain the best-fit measurement models from the variables.Structural Equation Modelling (SEM) was used to test the hypotheses.The findings show that there are significant relationships between self-knowledge (SK) and career decision-making (CDM),and occupational exploration (OE)and career decision-making (CDM).The result for testing invariance of a structural model for multi-group analysis showed a validation model of self-knowledge (SK),occupational exploration (OE) and career decision making (CDM).Based on this finding,it is imperative for graduating university students to enhance their self-knowledge,occupational exploration,and self-confidence in order to portray a positive attitude that will lead to work-related engagement.